Paracoccidioides brasiliensis recovered from the intestinal tract of three bats (artibeus lituratus) in Colombia, S.A. - Grose, E.; Tamsitt, J.R. (Medical Mycology, 1965)
A total of 243 bats belonging to six species were collected in the tropical zone of west central Colombia. Three individuals of Artibeus lituratus (2 males and 1 female) from Melgar, Colombia, harboured Paracoccidioides brasiliensis; cultures being taken directly from the intestinal tract. To our knowledge this is the first report of recovery of P. brasiliensis from animals. © 1965 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.
54 citations (Crossref) [2023-10-31]
Keywords: Animal; Blastomycosis; Chiroptera; Colombia; Intestinal Diseases; Parasitic; animal; animal disease; article; bat; blastomycosis; dept.bio; intestine infection